The The Influence of Online Marketing and Product Quality on Competitiveness Micro: Small And Medium Enterprises (MSMEs) Apparel Products InWest Java - Saepudin; Ratnawati, Aryanti; Hamzah, Ari Muhamad; Acuviarta, Acuviarta (Adpebi Science Series, 2022)
Abstract PorpuseThis study aims to determine about factors Implementation of online marketing of apparel products, Competitiveness of apparel products at MSMEs and the effect of product quality and online marketing on the competitiveness of SMEs in Cimahi West Java. Research method used is descriptive associative method, with the formulation of the hypothesis: Online marketing and product quality have an effect on the competitiveness of apparel MSMEs in Cimahi. To test the hypothesis, a sample was used, in the form of SMEs who produce apparel as many as 52 people (using the Slovin formula with a standard error of 10%). Result :The coefficient of determination (R-Square) in total is 0.594. This means that the competitiveness of SMEs for apparel in Cimahi West Java is influenced by online marketing and product quality by 59.4%. The remaining 40.6% is influenced by other factors not examined. Simultaneous hypothesis testing (F test) with α 5%, the obtained t-count> t-table (35.817> 3.18), it can be concluded that online marketing and product quality have a significant effect on the competitiveness of clothing MSMEs. Keywords: online marketing1, product quality2, and competitiveness of MSMEs3.